ANALISIS GAYA BELAJAR SISWA DISLEKSIA - Fitri Siti Sundari; Cicih Handayani (Universitas Pakuan, 2020)
ANALYSIS OF LEARNING STYLE OF DYSLEXIAThis research applies case study research with a qualitative approach. The purpose of this study was to describe the findings on the learning styles of dyslexic students in Dago State Elementary School, Bogor Regency, 2018/2019. The subject of this study was one of the students who came from Dago State Elementary School, Bogor Regency, 2018/2019 academic year. This research was conducted in the odd semester of the 2018/2019 academic year. The procedure for collecting data and recording data is carried out through observation, interviews, and documentation. Data analysis techniques are carried out by the stage of data reduction, data presentation, and verification (conclusion drawing). The researcher uses credibility, transferability, dependability, and confirmability tests to obtain data validity. The results showed that the learning styles of dyslexic students at SDN Negeri Dago 02 showed kinesthetic learning styles, learning processes that required a lot of movement or physical activity. Based on the results of the study it can be concluded that dyslexia students have a kinesthetic learning style, during the learning process in the Rendi class it is easier to understand or capture lessons with activities or activities that involve a lot of motion or physical activity.